Léxico, cultura, tradição e modernidade: um retrato sociolingüístico do Congado MontesClarense - Oliveira, Sandra Ramos de (2009)
This investigation was aimed at identifying, analyzing and describing the lexical aspects used by the members of folk groups from Montes Claros through the construction of a lexical-semantic field of the congado Montesclarense, verifying how much it reports the social, historical and cultural reality of Catopês, Marujos and Caboclinhos groups which yearly do their festivities in August in this city. This analysis didn t have the intention of exausting the lexias related to the Fests. It limited to those ones which were found out in the chosen corpus which are connected to the relation between the lexicon and the culture in the formation of the linguistic identity of people from Montes Claros. This study was aimed at presenting the relation between the lexicon and culture, conceiving culture as a system of practices. It is through the lexical analysis that it intended to detect the social practices of Montes Claros Congado groups and evidence their relation with the local culture. It was adopted a sociolinguistics approach and the theoretical principles of lexicology and semantics, emphasizing the process of meaning construction. It was evidenced that in the songs creation of each group the meaning is determined by liguistic and non-linguistic elements, showing a semantic peculiarity which represents the way of thinking, behaving and living of Congadeiros.